Dampak Penggunaan Smartphone Dalam Perkembangan Kognitif Siswa Kelas V SDI Darul Huda - Tb M Qadar R; Sifta Firdiyah; Siti Mucliyana (UNIVERSITAS RAHARJA, 2020)
Cognitive Intelligence development is related to intellectual potential of the individual, the ability of think and problems solve. The cognitive aspect is also influenced by the development of the brain's central nerve cells. The use of smartphones in daily life can be felt by facilitating communication for its users and also as a means of entertainment, as well as a form ofintroduction to Science and technology for early generations as a means of technological literacy, the negative impacts caused such as, making addiction to children under age teenager, the level of desire to learn decreases when in school or at home and children will be lazy to move and ect. So there needs to be an introduction in the form of local content or additional subjects in schools, which direct the use of smartphones for students to progress in a positive direction.